PERSONNEL MOTIVATION AS AN IMPORTANT TOOL FOR EFFICIENT ENTERPRISES - BOKOVETS, VICTORIA; KULHANIK, OKSANA; APOSTOLOVA, V. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the issues of increasing the efficiency of motivation of enterprise personnel. The definition of the essence of the concept of "motivational mechanism in personnel management of the enterprise" is specified, the categories of material and intangible incentives are considered. The thesis is substantiated that the complex application by employers of methods of direct and indirect motivation allows to keep the staff and increase the efficiency of labor activity, helps to increase the inclusion of employees in the labor process. The priority types of material and intangible incentives for employees are summarized. Priority directions of the motivational mechanism which will allow to increase efficiency of system of management of the personnel of the enterprise and to improve the organization of social and labor relations between workers and employers are developed. In modern conditions, human resources are one of the most important elements in the enterprise. For the successful operation of any production and any company, regardless of the services it provides and the goods it produces, you need an efficient work team. The purpose of the article is to determine the directions of the system of motivation of personnel of domestic enterprises. The following general and special methods were used in the research process: abstract-logical and structural-logical analysis – for theoretical generalizations and clarification of the concepts of "personnel management", "personnel evaluation", statistical analysis method for analysis and identification of main trends and management system staff; graphical method – to illustrate the results of the study. The article considers the theoretical foundations of staff motivation, summarizes the existing types and methods of motivation. Motivation is one of the most important elements of the personnel management system, because it is through motivation that the company’s management manages to influence employees. Direct economic motivation today is the most important for most Ukrainians, because in an unstable economy, a decent wage is the basis for meeting basic human needs. However, indirect economic and non-economic motivations are also very important and ensure employee commitment to the company, increase job satisfaction, reduce staff turnover and, consequently, additional staff costs. The movement of personnel, the structure of personnel costs, growth rates (decrease) of nominal and real wages at industrial enterprises of Ukraine and the effectiveness of motivational measures are analyzed. The importance of non-financial factors in the process of staff motivation is substantiated. The scheme of diagnostics of the motivation system is developed. It is proposed to introduce a system of bonuses at domestic enterprises, which will improve labor productivity and product quality. The system of staff motivation has been improved by including the mandatory introduction of a motivational social package and modern innovative management methods, which will increase the economic efficiency of the enterprise.